Oxidative stress in ischemia and reperfusion: current concepts, novel ideas and future perspectives. (2017) - Sinning, Christoph; Westermann, Dirk; Clemmensen, Peter
Oxidative stress remains a major contributor to myocardial injury after ischemia followed by reperfusion (I/R) as the reperfusion of the myocardial infarction (MI) area inevitably leads to a cascade of I/R injury. This review focused on concepts of the antioxidative defense system and elucidates recent research using antioxidants like vitamin C, E and β-carotene or essential trace elements to activate compounds of antioxidative pathways in the circulation. In this context, important defense mechanisms like superoxide dismutase and glutathione peroxidase will be described. Furthermore, the different mechanisms through which myocardial protection can be addressed, like ischemic postconditioning in myocardial infarction or adjunctive measures like targeted temperature management as well as new theories, including the role of iron in I/R injury, will be discussed.